Produksi Hukum Islam di Jawa Abad ke-15: Studi Historis atas Peran Walisongo dalam Kesultanan Demak - Muflih Rofal; Dzulkifli Hadi Imawan (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2025)
As the first Islamic kingdom in Java, the Sultanate of Demak played a crucial role in integrating Islamic teachings with the pre-existing political and legal structures of the region. Far from being limited to religious rituals or spiritual concerns, the application of Islamic law in Demak extended into various aspects of governance, social regulation, and public ethics. This integration marked a significant transformation in Javanese society, as Islamic norms gradually began to influence decision-making processes, judicial practices, and administrative structures. One of the most significant features of the Demak period was the emergence of Islamic educational institutions, which served as centers for both religious instruction and intellectual development. These institutions not only provided a formal setting for the study of the Qur’an, Hadith, and fiqh (Islamic jurisprudence), but also helped shape a generation of scholars and leaders who would continue the process of Islamization throughout Java. At the heart of this intellectual and spiritual movement were the ulama, particularly the legendary Walisongo (Nine Saints), whose influence extended beyond religious teaching. Through da'wah (missionary work), educational outreach, and social leadership, the Walisongo helped embed Islamic legal and moral values into the everyday lives of the Javanese people. Their holistic approach combined law, ethics, and community welfare, thereby facilitating both spiritual growth and social harmony. The legacy of the Demak Sultanate, therefore, lies not only in its political achievements but also in its pivotal contribution to the institutionalization of Islamic law and education in Java’s historical landscape.